Characterization of In Vitro Expanded Virus-Specific T cells for Adoptive Immunotherapy against Virus Infection - Ono, Toshiaki; Fujita, Yuriko; Matano, Tetsuro; Takahashi, Satoshi; Morio, Tomohiro; Kawana-Tachikawa, Ai (Japanese Journal of Infectious Diseases, 2018)
Adoptive transfer of virus-specific T cells has emerged as a promising therapeutic approach for treatment of virus infections in immunocompromised hosts. Characterization of virus-specific T cells provides essential information about the curative mechanism of the treatment. In this study, we developed a T cell epitope mapping system for 718 overlapping peptides spanning 6 proteins of 3 viruses (pp65 and IE1 from cytomegalovirus; LMP1, EBNA1, and BZLF1 from Epstein-Barr virus; Penton from adenovirus). Peripheral blood mononuclear cells (PBMCs) from 33 healthy Japanese donors were stimulated with these peptides and virus-specific CD4+ and CD8+ T cells were expanded in vitro in the presence of interleukin (IL) 4 and IL7. A median of 13 (minimum–maximum, 2–46) peptides was recognized in the cohort. Both fresh and cryopreserved PBMCs were used for in vitro expansion. The expansion and breadth of T cell responses were not significantly different between the 2 PBMC sets. We assessed viral regions frequently recognized by T cells in a Japanese cohort that could become pivotal T cell targets for immunotherapy in Japan. We tested epitope prediction for CD8+ T cell responses against a common target region using a freely available online tool. Some epitopes were considered to be predictive.